2021
DOI: 10.1523/jneurosci.0419-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Organization of Neural Inputs from Spinal Motor Neurons to Extrinsic and Intrinsic Hand Muscles

Abstract: Our current understanding of synergistic muscle control is based on the analysis of muscle activities. Modules (synergies) in muscle coordination are extracted from electromyographic (EMG) signal envelopes. Each envelope indirectly reflects the neural drive received by a muscle; therefore, it carries information on the overall activity of the innervating motor neurons. However, it is not known whether the output of spinal motor neurons, whose number is orders of magnitude greater than the muscles they innervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
1
39
1
Order By: Relevance
“…The use of LIF neurons and local spike-driven plasticity rules opens up the possibility of implementing such architecture on neuromorphic chips, leading to an even more efficient online and wearable implementation. We considered muscles in the forearm (extrinsic), to target the use of myoelectric armbands and bracelets for monitoring users' activity [37,38], and in the hand (intrinsic), so far considered mainly in neurophysiology [36,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of LIF neurons and local spike-driven plasticity rules opens up the possibility of implementing such architecture on neuromorphic chips, leading to an even more efficient online and wearable implementation. We considered muscles in the forearm (extrinsic), to target the use of myoelectric armbands and bracelets for monitoring users' activity [37,38], and in the hand (intrinsic), so far considered mainly in neurophysiology [36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…To identify the motor neurons firing patterns of the investigated muscles and track the same motor neurons across multiple tasks, we concatenated the HD-sEMG signals of the recordings relative to each gesture and then decomposed the concatenated HD-sEMG as in [40]. Each group of 64 concatenated HD-sEMG signals corresponding to a recording grid of 64 electrodes was decomposed separately with the CKC algorithm [45] (Fig.…”
Section: B)mentioning
confidence: 99%
“…On the other hand, identification of MU discharges from noninvasively recorded high-density EMG (hdEMG) signals offers a detailed insight into the behavior of relatively large number of MUs (Holobar and Zazula, 2007;Negro et al, 2009;Tanzarella et al, 2021). These EMG decomposition techniques identify the MU discharge times and fully remove the effects of MUAPs from the recorded EMG signals (Holobar and Farina, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They also offer efficient control of MU identification accuracy (Holobar et al, 2014) and, therefore, control of the quality of the muscle activation estimation. Different approaches to muscle activation estimation from MU discharge patterns were also developed, including Principal Component Analysis of smoothed MU discharge rates (Negro et al, 2009), NMF of smoothed MU discharge rates (Tanzarella et al, 2021) and Cumulative Spike Train (CST) of identified MUs (Farina et al, 2014). Indeed, studies of simultaneous MU behavior in different muscles are increasing (Héroux et al, 2014;de Souza et al, 2018;Kranjec and Holobar, 2019;Davis et al, 2020;Potočnik et al, 2020;Cohen et al, 2021;Tanzarella et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation